2019
DOI: 10.21873/invivo.11508
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-sectional Survey of the Clinical Manifestations and Underlying Illness of Cough

Abstract: Aim: The aim of this study was to identify factors affecting the final diagnosis of cough. Materials and Methods: This study recruited 463 consecutive patients who visited five Japanese general hospitals due to cough from October 2006 to September 2007. Of these, 418 patients (90%) who completed a questionnaire designed to acquire data regarding clinical manifestations of cough were included. Results: Most patients with bronchial asthma had cough with seasonal variation and wheezing. Patients with gastro esoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Mello et al 17 reported that the characteristics, timing, and complications of chronic cough were unlikely to be useful in diagnosing chronic cough. In contrast, Otoshi et al 19 found that cough with seasonal variation was useful for diagnosing asthma and cough without daily or seasonal variation indicated gastroesophageal reflux disease. Everett and Morice 34 showed that a symptom complex that is characteristic of reflux cough can be identified.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Mello et al 17 reported that the characteristics, timing, and complications of chronic cough were unlikely to be useful in diagnosing chronic cough. In contrast, Otoshi et al 19 found that cough with seasonal variation was useful for diagnosing asthma and cough without daily or seasonal variation indicated gastroesophageal reflux disease. Everett and Morice 34 showed that a symptom complex that is characteristic of reflux cough can be identified.…”
Section: Discussionmentioning
confidence: 91%
“…Studies on whether the clinical characteristics of cough could be useful for the diagnosis of chronic cough are limited. 17 , 18 , 19 Hence, we aimed to analyze different cough characteristics, concomitant symptoms, and medical history in diagnosing the causes of chronic cough with a single underlying cause.…”
mentioning
confidence: 99%
“…Cough is categorized according to the duration of symptoms: acute cough (0–2 weeks), subacute cough (3–7 weeks) and chronic cough (more than 8 weeks) 2 . In a previous study, we revealed that each type of cough occurred in 19%, 38% and 43% of all the patients who visited our hospitals for cough (n = 207) 3 . Cough greatly impacts our daily lives.…”
Section: Introductionmentioning
confidence: 82%
“…Cough is categorized according to the duration of symptoms: acute cough (0-2 weeks), subacute cough (3-7 weeks) and chronic cough (more than 8 weeks) [2]. In a previous study, we revealed that each type of cough occurred in 19%, 38% and 43% of all the patients who visited our hospitals for cough (n=207) [3]. Cough greatly impacts our daily lives.…”
Section: Introductionmentioning
confidence: 99%